The relationship between dialysis adequacy and the rate of change in uric acid level by hemodialysis - Bozkurt, Oktay; Topal, Cevat; İnanç, Mevlüde (Journal of Surgery and Medicine, 2018)
Aim: Although one of the commonly used methods for determining dialysis adequacy is the urea kinetic model, it is not the gold standard. Different parameters are needed to determine dialysis adequacy. In our study, we investigated the relationship between urea reduction rate (URR) and Kt/V which are used to assess dialysis adequacy and the rate of change in uric acid, a purine metabolite, by hemodialysis. Methods: A total of 133 patients who had undergone hemodialysis treatment due to renal failure between March 2010 and September 2010 were evaluated retrospectively. Urea kinetic modeling was used to measure dialysis adequacy. The following formula was used to do this; Kt/V=-ln(R-0.008xT)+(4-3.5xR)xUF/W[R; postdialysis blood ureanitrogen (BUN)/predialysis BUN, T; duration of dialysis (hr), UF; total ultrafiltration during dialysis (L), W; patient weight after dialysis (kg)]. The urea reduction rate was calculated using the formula; URR(%)=100x(1-postdialysis BUN/predialysis BUN). Uric acid reduction rate (UARR) was calculated using the formula; UARR(%)=100x(1-Uric acid after/Uric acid before). The relationship between URR and Kt/V ratios which are used to assess dialysis adequacy and UARR is evaluated. Results: Median urea, uric acid and creatinine reduction rates were 72%, 74% and 63.9%, respectively. There was a statistically significant correlation between reduction rates of uric acid, creatinine and urea after dialysis (p<0.001). There was a statistically significant relationship between URR and Kt/V which are used to assess dialysis adequacy,and UARR (p<0,001). According to the ROC analysis in our study, we defined UARR value that will demonstrate dialysis adequacy as at least 65.8% (sensitivity 97.9% and specificity 82.6%, area under the ROC curve=0.880, p<0.001). Conclusion: A significant relationship was found between the URR and Kt/V ratios which are used to assess dialysis adequacy and UARR. We also determined in our study that the UARR value that shows dialysis adequacy should be at least 65.8%. To our knowledge, this is the first study to evaluate the relationship between UARR and dialysis adequacy. However, thefindings need to be confirmed by large, prospective, clinical trials.